Increasing Interest and Learning Outcomes of Elementary School Students in Style Material Through Blended Learning - Ageng Satria Pamungkas; Nur Halimah (P3M IAI Nusantara Batang Hari, 2021)
This study aims to increase student interest and learning outcomes in style material through a blended learning model for fourth grade students at SDIP Tunas Bangsa Banjarnegara. The research subjects were 24 grade IV students at SDIP Tunas Bangsa. This research method is a type of research that is collaborative classroom action research. This research was conducted in two cycles. Each cycle has 4 stages, namely planning, implementing, observing, and reflecting on actions. The indicator of success in this classroom action research is if the class average is ≥70 with a classical completeness percentage of 85%. The results of the study showed that using the blended learning model in science lessons on Gaya could increase the interest and learning outcomes of fourth grade students at SDIP Tunas Bangsa Banjarnegara. It can be seen that the average interest score in cycle I was 64.9, increasing in cycle II to 81.22. While the score of student learning outcomes in cycle I was 63% complete KKM increased to 87% completed in cycle II. After implementing Blended Learning, the data on increasing interest in learning can significantly increase the interest and learning achievement of grade IV students at SDIP Tunas Bangsa, Banjarnegara district.